2010
DOI: 10.1186/1479-5876-8-20
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of mitoxantrone, estramustine and vinorelbine or bcl-2 modulation with 13-cis retinoic acid, interferon and paclitaxel in patients with metastatic castrate-resistant prostate cancer: ECOG 3899

Abstract: BackgroundTo test the hypothesis that modulation of Bcl-2 with 13-cis retinoic acid (CRA)/interferon-alpha2b (IFN) with paclitaxel (TAX), or mitoxantrone, estramustine and vinorelbine (MEV) will have clinical activity in men with metastatic castrate-resistant prostate cancer (CRPC).Methods70 patients were treated with either MEV (Arm A) in a 3-week cycle or CRA/IFN/TAX with an 8-week cycle (Arm B). Patients were assessed for response, toxicity, quality of life (QOL), and the effect of treatment on Bcl-2 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Bcl-2 is an antiapoptotic protein that is overexpressed in multiple tumors including prostate cancer, thereby conferring resistance to therapies that induce apoptosis, such as ADT [3, 4]. Based upon preclinical data suggesting that the efficacy of ADT could be enhanced by combing ADT with AT-101, we undertook the current single arm phase II study in men with newly diagnosed hormone sensitive metastatic disease in order to determine if the combination could improve upon a novel clinical endpoint in this disease setting, the rate of patients achieving an undetectable PSA after 7 months of ADT and AT-101.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bcl-2 is an antiapoptotic protein that is overexpressed in multiple tumors including prostate cancer, thereby conferring resistance to therapies that induce apoptosis, such as ADT [3, 4]. Based upon preclinical data suggesting that the efficacy of ADT could be enhanced by combing ADT with AT-101, we undertook the current single arm phase II study in men with newly diagnosed hormone sensitive metastatic disease in order to determine if the combination could improve upon a novel clinical endpoint in this disease setting, the rate of patients achieving an undetectable PSA after 7 months of ADT and AT-101.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in prostate cancer tissue demonstrated that Bcl-2 is over-expressed in most patients with castration-resistant prostate cancer (CRPC) [3, 4]. In animal models, Bcl-2 is responsible for drug resistance to chemotherapy and ADT, and modulation of Bcl-2 improves sensitivity [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoids can decrease expression of Bcl-2, and the combination of 13-cis retinoic acid and interferon enhanced the effect of paclitaxel chemotherapy, resulting in that this combination can be safely administered in phase I studies [48]. Interactions between polyamines and retinoids can regulate retinoid-induced apoptosis in Jurkat cells [23]; similarly, retinoic acid activates transglutaminase that conjugates with putrescine, probably leading to a simultaneous inhibition of DNA synthesis in PH-animals [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mitoxantrone may induce cell senescence [19]. Side effects of mitoxantrone include leukemia [20], cardiotoxicity [21], anemia [21] and thrombosis [22,23,24,25,26,27]. …”
Section: Introductionmentioning
confidence: 99%